Contacts, Opportunities, and Criminal Enterprise - Morselli, Carlo, 1969- (Book collections on Project MUSE., 2005)
"Based on two case studies of criminal careers in international cannabis smuggling and Cosa Nosta racketeering, the book proposes a social network framework to study the underlying social relationships influencing achievement in crime. Carlo Morselli further utilizes this relational approach to illustrate how early success and long-term survival in criminal enterprise are achieved, and how criminals' networks of contacts and opportunities can insulate them from potentially career-damaging forces such as law enforcement and fellow criminals."--Jacket.